2009
DOI: 10.2337/db08-1372
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Type 2 Diabetes in Obese Youth

Abstract: OBJECTIVE— Some obese youth with a clinical diagnosis of type 2 diabetes have evidence of islet cell autoimmunity with positive autoantibodies. In this study, we investigated the differences in insulin sensitivity and secretion between autoantibody-negative (Ab − ) and -positive (Ab + ) youth with clinically diagnosed type 2 diabetes in comparison with control subjects. RESEARCH DESIGN AND METHODS— Sixteen Ab − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 28 publications
5
110
1
Order By: Relevance
“…The activities of both glucose-6-phosphatase and fructose-1, 6-bisphosphatase are increased in the liver during the diabetic condition [43] . Treatment with M. emarginata has appreciably normalized the activity of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activities of both glucose-6-phosphatase and fructose-1, 6-bisphosphatase are increased in the liver during the diabetic condition [43] . Treatment with M. emarginata has appreciably normalized the activity of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The high concentration of blood glucose and other biochemical abnormalities result from a deficiency of 毬-cells of the endocrine pancreas and/or from a sub sensitivity to insulin in target cells [4][5][6] . A worldwide survey reported that the estimated incidence of diabetes and projection for year 2030 is 350 million [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, type 2 diabetes is another syndrome, most frequently seen in obese adults, and is a consequence of the development over time of a target cell resistance to the action of the natively produced insulin. Now this distinction is becoming unclear again since an increased incidence of sedentary lifestyles, synergized with excessive calorific intake, has led to an increase in the frequency of obese children becoming type 1 diabetics [1]. In their review presented in this issue, Coppieters and von Herrath propose a "continuous spectrum", with type 1 and type 2 diabetes positioned at opposite ends.…”
Section: Barriers To Progress Into Diabetes Researchmentioning
confidence: 99%
“…Failure of β-cells to produce adequate amounts of insulin is attributed to high levels of free fatty acids present in the plasma. This results in a decrease of glucose transportation into the muscle cells, thereby increasing levels of glucose and fat in the blood plasma, eventually causing hyperglycemia and lipid oxidation, which can be controlled by the anti-oxidative property of dandelion [93,94]. In a study evaluating the effects of anti-oxidant on C57BL/6J mice fed a high-fat and -cholesterol diet using leafy mixed vegetable extracts (including dandelion), a significant drop in lipid peroxidation in various organs including the liver was observed [95].…”
Section: Anti-oxidative Propertiesmentioning
confidence: 99%